Effect of plasma torus density variations on the morphology and brightness of the Io footprint. Issue 5 (28th May 2014) - Payan, A. P.; Rajendar, A.; Paty, C. S.; Crary, F.
Abstract We develop a 2‐D‐layered model of the Io plasma torus to study the apparent "shutoff" of the Io footprint in 2007, when it disappeared beneath a region of diffuse emissions, roughly coincident with a massive eruption of Tvashtar Paterae. First, we investigate the effects of Io's location in the plasma torus and validate our model results against Hubble UV observations of the Io footprint. We are able to qualitatively reproduce variations in the morphology of the footprint due to Io's changing latitudinal location with respect to the center of the plasma torus, capturing the bright leading spot and the dimmer tail. Then, we consider the effects of an increase in the local plasma density on the brightness and morphology of the Io footprint. Our results show a correlation between a local density increase in the plasma torus and the dimming of the Io footprint as observed in 2007. In particular, we find that a local density enhancement at Io of fivefold compared to the nominal value is sufficient to produce the observed shutoff of the footprint.